Human Herpesvirus 6 Encephalitis in Immunocompetent and Immunocompromised Hosts. Issue 2 (12th March 2021) - Berzero, Giulia; Campanini, Giulia; Vegezzi, Elisa; Paoletti, Matteo; Pichiecchio, Anna; Simoncelli, Anna Maria; Colombo, Anna Amelia; Bernasconi, Paolo; Borsani, Oscar; Di Matteo, Angela; Rossi, Virginia; Foiadelli, Thomas; et al.
Abstract : Objective: The aim of this study was to analyze the clinical, radiologic, and biological features associated with human herpesvirus 6 (HHV-6) encephalitis in immunocompetent and immunocompromised hosts to establish which clinical settings should prompt HHV-6 testing. Methods: We performed a retrospective research in the virology database of Fondazione IRCCS Policlinico San Matteo (Pavia, Italy) for all patients who tested positive for HHV-6 DNA in the CSF and/or in blood from January 2008 to September 2018 and separately assessed the number of patients meeting the criteria for HHV-6 encephalitis in the group of immunocompetent and immunocompromised hosts. Results: Of the 926 patients tested for HHV-6 during the period of interest, 45 met the study criteria. Among immunocompetent hosts (n = 17), HHV-6 encephalitis was diagnosed to 4 infants or children presenting with seizures or mild encephalopathy during primary HHV-6 infection (CSF/blood replication ratio <<1 in all cases). Among immunocompromised hosts (n = 28), HHV-6 encephalitis was diagnosed to 7 adolescents/adults with hematologic conditions presenting with altered mental status (7/7), seizures (3/7), vigilance impairment (3/7), behavioral changes (2/7), hyponatremia (2/7), and anterograde amnesia (1/7). Initial brain MRI was altered only in 2 patients, but 6 of the 7 had a CSF/blood replication ratio >1. Conclusions: The detection of a CSF/blood replication ratio >1 represented a specific feature of immunocompromised patients with HHV-6 encephalitis and could be of special help to establish a diagnosis of HHV-6 encephalitis in hematopoietic stem cell transplant recipients lacking radiologic evidence of limbic involvement.